Hyaluronan-based extracellular matrix under conditions of homeostatic plasticity - Valenzuela, Juan Carlos; Heise, Christopher; Franken, Gilbert; Singh, Jeet; Schweitzer, Barbara; Seidenbecher, Constanze I.; Frischknecht, Renato (Philosophical Transactions of the Royal Society B-Biological Sciences, 2014)
Neuronal networks are balanced by mechanisms of homeostatic plasticity, which adjusts synaptic strength via molecular and morphological changes in the pre- and post-synapse. Here, we wondered whether the hyaluronic acid-based extracellular matrix (ECM) of the brain is involved in mechanisms of homeostatic plasticity. We hypothesized that the ECM, being rich in chondroitin sulfate proteoglycans such as brevican, which are suggested to stabilize synapses by their inhibitory effect on structural plasticity, must be remodelled to allow for structural and molecular changes during conditions of homeostatic plasticity. We found a high abundance of cleaved brevican fragments throughout the hippocampus and cortex and in neuronal cultures, with the strongest labelling in perineuronal nets on parvalbuminpositive interneurons. Using an antibody specific for a brevican fragment cleaved by the matrix metalloprotease ADAMTS4, we identified the enzyme as the main brevican-processing protease. Interestingly, we found ADAMTS4 largely associated with synapses. After inducing homeostatic plasticity in neuronal cell cultures by prolonged network inactivation, we found increased brevican processing at inhibitory as well as excitatory synapses, which is in line with the ADAMTS4 subcellular localization. Thus, the ECM is remodelled in conditions of homeostatic plasticity, whichmay liberate synapses to allow for a higher degree of structural plasticity.
CRIS-Team Scopus Importer:2022-08-05
Keywords: ADAMTS4; Brevican; Extracellular proteolysis; Mmp; Perineuronal nets; Synaptic plasticity